2021
DOI: 10.2147/cmar.s317319
|View full text |Cite
|
Sign up to set email alerts
|

Myelin and Lymphocyte Protein (MAL): A Novel Biomarker for Uterine Corpus Endometrial Carcinoma

Abstract: Purpose Myelin and lymphocyte protein (MAL) plays an essential role in esophageal cancer, classic Hodgkin’s lymphoma and breast cancer. However, its role in uterine corpus endometrial carcinoma (UCEC) has not been explored. Therefore, the current study sought to explore the role of MAL in UCEC. Patients and Methods Differentially expressed genes (DEGs) were identified by using Limma package in R based on TCGA-UCEC data. Kaplan–Meier plotter analysis was performed to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…However, in the case of STAD, one study showed that MAL hypermethylation, which was accompanied by MAL mRNA downmodulation [75], has a favorable prognosis, while MAL mRNA downmodulation correlated with an unfavorable prognosis in another study [76]. Consistent with the analysis illustrated in Figure 7, the use of IHC confirmed that a high level of MAL expression is associated with unfavorable outcome in UCEC [152]. With regard to the other MAL-family members, IHC analysis confirmed that high levels of MAL2 [99] and MYADM [117] are associated with poor outcome in PAAD and STAD, respectively.…”
Section: Mal-family Genes As Prognostic Cancer Biomarkers: Analysis O...supporting
confidence: 62%
See 1 more Smart Citation
“…However, in the case of STAD, one study showed that MAL hypermethylation, which was accompanied by MAL mRNA downmodulation [75], has a favorable prognosis, while MAL mRNA downmodulation correlated with an unfavorable prognosis in another study [76]. Consistent with the analysis illustrated in Figure 7, the use of IHC confirmed that a high level of MAL expression is associated with unfavorable outcome in UCEC [152]. With regard to the other MAL-family members, IHC analysis confirmed that high levels of MAL2 [99] and MYADM [117] are associated with poor outcome in PAAD and STAD, respectively.…”
Section: Mal-family Genes As Prognostic Cancer Biomarkers: Analysis O...supporting
confidence: 62%
“…Thus, exogenously-expressed MAL in breast [67], esophageal [129], cervical [87], colorectal [113], lung [84], and head and neck [71] cancer cell lines reduced cell migration and invasion, or increased apoptosis, and reduced tumor size in nude mice [71,84,129]. Similar effects were observed for exogenous MAL2 in prostate [152], pancreatic [99], lung [149], and liver [108] cancer cells; for exogenous MALL in colorectal cancer cells [113]; and for CMTM8 in liver [153], pancreatic [119], and urothelial [116] cancer cells. These observations suggest that at least some of the MAL-family genes downmodulated in tumors might have a tumor-suppressor function in specific organs and tissues.…”
Section: The Mal-protein Family As Tumor Suppressorssupporting
confidence: 53%
“…Advances in detection mean that most patients with UCEC can be diagnosed or treated at an early stage, improving survival. However, a significant number of patients are diagnosed at advanced stage or harbor occult metastatic lesions, causing tumor recurrence because of the limited response to therapies [ 34 ]. In addition, conventional diagnostic approaches provide limited prognostic information that could aid clinical judgement and provide therapeutic guidance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mal family encompasses members that are widely distributed across various bodily systems, with their involvement in the digestive, respiratory, urinary and circulatory systems being successively uncovered. These proteins play crucial roles in tumorigenesis signaling pathways and cell cycle regulation, thereby influencing tumor development and patient prognosis (38,39,42,68,136,164). However, the current understanding of their specific molecular mechanisms remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting its tumor suppressor activity includes ectopic MAL expression inhibiting growth and reducing viability of cancer cells in nude mouse models, blocking G1/S transition and increasing Fas-mediated apoptosis (32,(62)(63)(64)(65)(66)(67). However, MAL acts as an oncogenic factor in endometrial carcinoma and certain lymphomas, such as thymic large B cell lymphomas but not in nodal diffuse large B cell lymphomas (39,(68)(69)(70)(71)(72).…”
Section: Mal/vip17mentioning
confidence: 99%